2022
DOI: 10.3897/zookeys.1117.83539
|View full text |Cite
|
Sign up to set email alerts
|

A new species of the genus Prosopistoma Latreille, 1833 (Ephemeroptera, Prosopistomatidae) from Morocco

Abstract: We describe a new species of Prosopistoma collected in the High Atlas Mountains of Morocco. Prosopistoma maroccanumsp. nov. appears to be morphologically more similar to the European highly endangered P. pennigerum (Müller, 1785) than to the other Maghrebian species, P. alaini Bojkova & Soldán, 2015. A gene tree including the few available barcode sequences of Palearctic Prosopistoma specimens is provided. Possible affinities with West African species are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A similar situation occurred with the recently described baetid species Baetis rifensis El Yaagoubi, Vuataz & Gattolliat, 2023 from Morocco. Its closest COI sequences were from three specimens sampled in the Iberian Peninsula, but in this case, the minimum p-distance between the Moroccan and Iberian lineages was higher (3.2%; El Yaagoubi et al 2023 ).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…A similar situation occurred with the recently described baetid species Baetis rifensis El Yaagoubi, Vuataz & Gattolliat, 2023 from Morocco. Its closest COI sequences were from three specimens sampled in the Iberian Peninsula, but in this case, the minimum p-distance between the Moroccan and Iberian lineages was higher (3.2%; El Yaagoubi et al 2023 ).…”
Section: Discussionmentioning
confidence: 74%
“… concinnum ]. Since then, a large number of surveys have been carried out to augment this initial list with an additional 35 species, resulting in a total species richness of 37 taxa, which constitutes more than 68% of Morocco’s Ephemeroptera ( Dakki and El Agbani 1983 ; Giudicelli and Dakki 1984 ; El Alami and Dakki 1998 ; El Alami et al 2000 , 2022a ; Kaltenbach et al 2022 ; Gattolliat et al 2023 ; El Alami et al 2023 ; El Yaagoubi et al 2023 ). These investigations have collected no less than three new species from the Rif, including Habrophlebia dakkii sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to assess the impact of climate change, human disturbances and pollution on aquatic macroinvertebrates, studies have been carried out over the different geographical Moroccan areas; the main goal was to evaluate the evolution of the mayfly community between the 1980s and the present days by prospecting selected stations in Haut Sebou (Zerrouk et al 2021), Moulouya (Mabrouki et al 2017), Ourika (Zuedzang Abessolo et al 2021 and Rifian watersheds (El Bazi et al 2017;Khadri et al 2017;Guellaf et al 2021).These recent studies of the main Moroccan watersheds confirms the presence of some species never reported since their original descriptions and increase the known distribution of others. Moreover, the specific diversity could increase with the verification of some doubtful identifications through genetic analysis, and the discovery of new species such as the recent description of Prosopistoma maroccanum (El Alami et al 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…During the last two decades, important improvements were made in the knowledge of North African mayflies. A few new species of Baetidae, Leptophlebiidae, Heptageniidae, and Prosopistomatidae were described from Tunisia, Algeria, and Morocco (Soldán et al 2005;Zrelli et al 2011;Benhadji et al 2018;Kechemir et al 2020;Dambri et al 2022;El Alami et al 2022b), and new reports were provided for countries or basins, especially for Tunisia (Zrelli et al 2011(Zrelli et al , 2012(Zrelli et al , 2016, East and West Algeria (Benhadji et al 2020;Samraoui et al 2021a, b), and Morocco (Khadri et al 2017;Mabrouki et al 2017;El Alami et al 2022a;Zerrouk et al 2021). A few species were morphologically revised including in some cases the description of previously unknown stages (Soldán et al 2005;Zrelli et al 2012;Godunko et al 2018).…”
Section: Introductionmentioning
confidence: 99%